2012
DOI: 10.1128/aem.00165-12
|View full text |Cite
|
Sign up to set email alerts
|

A Loss-of-Function Mutation in the PAS Kinase Rim15p Is Related to Defective Quiescence Entry and High Fermentation Rates of Saccharomyces cerevisiae Sake Yeast Strains

Abstract: b Sake yeast cells have defective entry into the quiescent state, allowing them to sustain high fermentation rates. To reveal the underlying mechanism, we investigated the PAS kinase Rim15p, which orchestrates initiation of the quiescence program in Saccharomyces cerevisiae. We found that Rim15p is truncated at the carboxyl terminus in modern sake yeast strains as a result of a frameshift mutation. Introduction of this mutation or deletion of the full-length RIM15 gene in a laboratory strain led to a defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
50
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 45 publications
13
50
0
1
Order By: Relevance
“…The differences in gene expression and the physiological responses are reminiscent of the observations of Watanabe et al (41), who analyzed the effects of a mutated form of the PAS kinase RIM15 in sake yeast. They showed that the altered form of RIM15 reduced the yeast stress response and the amount of storage carbohydrate and enhanced the fermentation rate.…”
Section: Discussionmentioning
confidence: 82%
“…The differences in gene expression and the physiological responses are reminiscent of the observations of Watanabe et al (41), who analyzed the effects of a mutated form of the PAS kinase RIM15 in sake yeast. They showed that the altered form of RIM15 reduced the yeast stress response and the amount of storage carbohydrate and enhanced the fermentation rate.…”
Section: Discussionmentioning
confidence: 82%
“…In sake yeast strain K701, unknown defects in the latter mechanism might have caused the observed decrease in the activities of Adr1p and Cat8p. We postulate that the Rim15p-Msn2/4p pathway, which is specifically inactivated in modern sake strains, 3,4) is indirectly involved in the maintenance of Adr1p and Cat8p activities. As shown in Table 2, however, deletion of the RIM15 gene did not decrease the ADH2 mRNA level in X2180-1A.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that defects in the stress responses mediated by Rim15p, 3) Msn2/ 4p, 4) and Hsf1p 52) contribute to enhancement of the initial fermentation rate in modern sake yeast strains. These findings, together with our present results, indicate that sake yeast has multiple cellular functions that have been impaired during years of selection and domestication, and that are unnecessary for or negatively affect efficient alcoholic fermentation.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations